(untitled) (World Science, 2019)
There was found out an expression of alterations of figure of liver function at patients with postoperative sternomediastenitis. There were revealed hupoproteinemia and dysproteinemia. Their degree was connected with disturb has of liver function. There data shows necessary of conduction of complex treatment of postoperative sternomediastenitis in consideration of disturbances of liver function.